2007
DOI: 10.2139/ssrn.1082840
|View full text |Cite
|
Sign up to set email alerts
|

Optimization in a Simulation Setting: Use of Function Approximation in Debt Strategy Analysis

Abstract: of the Bank of Canada for useful comments. We would also like to thank Jeremy Graveline from the University of Minnesota and Mark Reesor from the University of Western Ontario for helpful discussions. All thanks are without implication and we retain any and all responsibility for any remaining omissions or errors.iii AbstractThe stochastic simulation model suggested by Bolder (2003) for the analysis of the federal government's debt-management strategy provides a wide variety of useful information. It does not,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Sephton [64], determined that MARS method is more successful than probit method [65] to predict the recession. Similar to this study, Bolder and Rubin [66], concluded that MARS method gives better results to define the best debt strategy in comparison with Kernel regression analysis. Moreover, Muzır [67], made a study about credit risk of Turkish banks and defined that MARS method measures this risk better than the logistic regression [68] analysis.…”
Section: Methodology: Mars Methodssupporting
confidence: 81%
“…Sephton [64], determined that MARS method is more successful than probit method [65] to predict the recession. Similar to this study, Bolder and Rubin [66], concluded that MARS method gives better results to define the best debt strategy in comparison with Kernel regression analysis. Moreover, Muzır [67], made a study about credit risk of Turkish banks and defined that MARS method measures this risk better than the logistic regression [68] analysis.…”
Section: Methodology: Mars Methodssupporting
confidence: 81%
“…While the SALM objective may be clearly stated, optimization of this objective crucially depends on the specification of the government's objective function. Simulation estimates based on various methods show that MARS outperforms other methods, particularly when the objective function is highly dimensional and nonlinear and there is a lack of a large number of observations (Bolder and Rubin, 2007). 19 Thus, given uncertainty about the complexity of the government's objective function, the MARS method allows significant flexibility in its estimation.…”
Section: Multivariate Adaptive Regression Splines (Mars) Methodsmentioning
confidence: 99%
“…In their simulations,Bolder and Rubin (2007) compare estimates of the ordinary least squares (OLS), nonparametric kernel regression (NKR), the projection pursuit regression (PPR), and MARS. They find that the goodness of fit of the NKR and PPR methods deteriorate quickly for even simple parabolic functions as their dimension increases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The approach we selected is termed Multiple Adaptive Regression Splines (MARS), which is a function-approximation technique based on the recursivepartitioning algorithm. The basic idea behind this technique is to define piecewise linear spline functions on an overlapping partition of the domain (Bolder and Rubin (2007) provide a detailed description of the MARS algorithm). As such, the MARS combination scheme can be considered an example of a mathematically complicated nonparametric, nonlinear aggregation of our four alternative models.…”
Section: : Marsmentioning
confidence: 99%